2007
DOI: 10.1186/1750-1172-2-40
|View full text |Cite
|
Sign up to set email alerts
|

Hypophosphatasia

Abstract: Hypophosphatasia is a rare inherited disorder characterized by defective bone and teeth mineralization, and deficiency of serum and bone alkaline phosphatase activity. The prevalence of severe forms of the disease has been estimated at 1/100 000.The symptoms are highly variable in their clinical expression, which ranges from stillbirth without mineralized bone to early loss of teeth without bone symptoms. Depending on the age at diagnosis, six clinical forms are currently recognized: perinatal (lethal), perina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
270
2
24

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 259 publications
(302 citation statements)
references
References 72 publications
5
270
2
24
Order By: Relevance
“…TNAP has been shown to hydrolyze the mineralization inhibitor PP i thereby maintaining proper bone mineralization [330]. Accordingly, mutations in the TNAP gene that cause impairment or loss of functional activity lead to hypophosphatasia in humans [486,487]. Similarly, TNAP knockout mice (Akp2−/−) accumulate extracellular PP i , reveal hypomineralization [488][489][490][491], and can serve as a model for the infantile form of hypophosphatasia [492].…”
Section: Substrates and Catalytic Propertiesmentioning
confidence: 99%
“…TNAP has been shown to hydrolyze the mineralization inhibitor PP i thereby maintaining proper bone mineralization [330]. Accordingly, mutations in the TNAP gene that cause impairment or loss of functional activity lead to hypophosphatasia in humans [486,487]. Similarly, TNAP knockout mice (Akp2−/−) accumulate extracellular PP i , reveal hypomineralization [488][489][490][491], and can serve as a model for the infantile form of hypophosphatasia [492].…”
Section: Substrates and Catalytic Propertiesmentioning
confidence: 99%
“…17 Two more genes, the tissue-nonspecific alkaline phosphatase gene (ALPL, 1p36.12, OMIM# 171760) and human orthologue of the mouse progressive ankylosis gene (ANKH, 5p15.1, OMIM# 605145) have been implicated in calcium and ePPi/Pi homeostasis. [17][18][19] It should be mentioned that although the role of ENPP1 in energy metabolism and fat tissue physiology has been extensively discussed in the scientific literature, 20 the potential relevancy of its partners in bone mineralization, that is ANKH and ALPL, to adipose tissue and OB etiology has hardly been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Correlations of genotype and phenotype have been reported on the basis of clinical data of the patients with hypophosphatasia, enzymatic activity and computerassisted modeling. 2 We previously reported that the most and the second-most frequent mutations in Japanese patients are T1559del and F310L, respectively. 5 These mutations are renamed to c.1559delT and p.F327 L, respectively, based on the recent standardized nomenclature.…”
mentioning
confidence: 97%